2011
DOI: 10.1128/jb.01191-10
|View full text |Cite
|
Sign up to set email alerts
|

dnaX36 Mutator of Escherichia coli : Effects of the τ Subunit of the DNA Polymerase III Holoenzyme on Chromosomal DNA Replication Fidelity

Abstract: The Escherichia coli dnaX36 mutant displays a mutator effect, reflecting a fidelity function of the dnaXencoded subunit of the DNA polymerase III (Pol III) holoenzyme. We have shown that this fidelity function (i) applies to both leading-and lagging-strand synthesis, (ii) is independent of Pol IV, and (iii) is limited by Pol II.The mechanisms by which organisms achieve a high accuracy of DNA replication are of ongoing interest. Replication of the chromosome of the bacterium Escherichia coli is performed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…DNA polymerase III holoenzyme (Pol III HE), the major replicative DNA polymerase in Escherichia coli, is a large complex of 17 subunits [2,3]. It has been shown that some mutations in the dnaX gene which encodes the subunit of Pol III HE lead to a mutator phenotype [4][5][6]. Also in Saccharomyces cerevisiae the accessory subunits of the main replicases have been demonstrated to affect the fidelity of DNA replication.…”
Section: Introductionmentioning
confidence: 99%
“…DNA polymerase III holoenzyme (Pol III HE), the major replicative DNA polymerase in Escherichia coli, is a large complex of 17 subunits [2,3]. It has been shown that some mutations in the dnaX gene which encodes the subunit of Pol III HE lead to a mutator phenotype [4][5][6]. Also in Saccharomyces cerevisiae the accessory subunits of the main replicases have been demonstrated to affect the fidelity of DNA replication.…”
Section: Introductionmentioning
confidence: 99%
“…In certain cases this contribution may lead to improved fidelity, when the accessory DNA polymerase is accurate (e.g., proofreading-proficient polymerases), while in other cases this may lead to lower fidelity when the polymerase is error-prone. Examples of both effects have been demonstrated [17]. …”
Section: Introductionmentioning
confidence: 99%
“…E. coli contains 5 different DNA polymerases of which DNA polymerase III is the main replicative polymerase responsible for chromosomal duplication (DNA polymerase III holoenzyme, HE). DNA polymerase II can play an important fidelity role by acting as a back-up proofreader for errors created by Pol III [1,7,10]. In contrast, Pol IV and Pol V, when present in amplified amounts, can reduce replication fidelity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is attractive to speculate that improved lagging-strand fidelity results from the more dissociative properties of the polymerase in this strand, permitting more efficient proofreading (note that proofreading is essentially a dissociative process in which the primer terminus is moved from the polymerase active site to the distant exonuclease site). Alternatively, the dissociative character of the lagging-strand polymerase may lead to increased removal of the terminal mismatch by the exonuclease of Pol II, which has been shown to proofread for Pol III under some conditions [12, 13, 34, 35] or by a third copy of Pol III that has been proposed to be present at the replication fork [36]. …”
Section: Discussionmentioning
confidence: 99%